2011
DOI: 10.1210/jc.2010-2253
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat Diet Elicits Differential Responses in Genes Coordinating Oxidative Metabolism in Skeletal Muscle of Lean and Obese Individuals

Abstract: These findings indicate a differential response to a lipid stimulus in the skeletal muscle of lean and insulin resistant obese humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 31 publications
7
63
1
Order By: Relevance
“…In addition, previous studies demonstrated that HFD increases fat oxidation in lean subjects (8,26, 33, 34) but not in obese or previously obese subjects (2,40). Furthermore, a 5-day HFD increased the expression levels in skeletal muscle of genes related to fatty acid oxidation in lean healthy subjects but not in obese subjects (7). These data suggest that changes in gene expression in response to HFD are important for the adaptation of skeletal muscle to HFD and that these changes may be associated with the interindividual variability of HFD on IMCL and insulin sensitivity.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, previous studies demonstrated that HFD increases fat oxidation in lean subjects (8,26, 33, 34) but not in obese or previously obese subjects (2,40). Furthermore, a 5-day HFD increased the expression levels in skeletal muscle of genes related to fatty acid oxidation in lean healthy subjects but not in obese subjects (7). These data suggest that changes in gene expression in response to HFD are important for the adaptation of skeletal muscle to HFD and that these changes may be associated with the interindividual variability of HFD on IMCL and insulin sensitivity.…”
mentioning
confidence: 87%
“…They found that skeletal muscle gene expression levels of important regulators for fat oxidation, namely, PPAR␣ and PGC-1␣, were lower in both the most insulin-sensitive group and the most insulinresistant group compared with the middle two quartiles. In addition, previous studies had demonstrated that HFD enhances fat oxidation (8,26,33,34) and the expression of genes related to fat oxidation in skeletal muscle (7) in lean subjects, but not in obese or previously obese subjects (2,7,40).…”
Section: E37 Imcl and Gene Expression In Muscle After High-fat Dietmentioning
confidence: 99%
“…Amino acid changes are thought to be largely due to anaplerosis, or the use of amino acid oxidative catabolism to replenish tricarboxylic acid cycle (TCA cycle) intermediates in the setting of incomplete β-oxidation (12)(13)(14)(15)(16). In myocytes from OB adults, there is reduced fatty acid oxidation, leading to elevations in long-and medium-chain acylcarnitines and anaplerosis, and decreased oxidative phosphorylation, indicating abnormalities in key energy pathways (13,(17)(18)(19). Similarly, in adipocytes from OB adults, there is decreased fatty acid oxidation, increased lipogenesis, and spared amino acid catabolism (13,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are the powerhouse of the cell, coupling the majority of energy derived from fuel substrates to ATP turnover and uncoupling less in the form of heat. In humans and rodents with obesity and related type 2 diabetes, fuel overload in the mitochondrial respiratory system and impaired mitochondrial oxidative capacity have been observed in energy-using organs and energy storage organs, such as skeletal muscle (SKM) [5][6][7] and white adipose tissue (WAT) [8,9]. Increasing cellular energy expenditure (EE) by decreasing mitochondrial coupling efficiency has been proposed to be an appealing therapeutic alternative [10,11].…”
Section: Introductionmentioning
confidence: 99%